Implementation of Standard Operating Procedures (SOP) for Acceptance of New Patients with Patient Satisfaction at Raja Musa Sungai Guntung Riau Regional Hospital in 2019 - Sukma Yunita; Kamaliah Ainun; Lina (Science Midwifery, 2020)
Admission of new patients who are not in accordance with standards is likely to reduce the quality of service and also reduce the level of patient satisfaction. This study aims to determine the relationship between the application of standard operating procedures (SOP) in new patient admissions with the level of patient satisfaction at the Raja Musa Sungai Guntung 2019 General Hospital. This study uses a correlation design, time series approach. The sample of this study was 30 new patients who came to the IGD Raja Musa Hospital, using purposive sampling technique. Collecting data using a questionnaire which is processed through the process of editing, coding, data entry, tabulating / processing. Data analysis with Chi Square test. Of the 30 respondents, it was found that the majority of respondents were dissatisfied 18 (60%) based on the level of satisfaction of implementing the SOP for new patient admission at Raja Musa Hospital, 13 respondents were quite good (43.3%). The result of p value analysis is 0.015 <0.05, then Ha is accepted and Ho is rejected. The conclusion of this study is that there is a relationship between the application of standard operating procedures (SOP) for new patient admissions with the level of patient satisfaction at the Raja Musa Sungai Guntung Riau Regional Hospital 2019.